Outer Membrane Vesicles From Fusobacterium nucleatum Switch M0-Like Macrophages Toward the M1 Phenotype to Destroy Periodontal Tissues in Mice - Chen, Gang; Sun, Qiang; Cai, QiaoLing; Zhou, HongWei (Frontiers in Microbiology, 2022)
Periodontitis is a chronic inflammatory oral disease that affects nearly 50% of all adults. Fusobacterium nucleatum (F. nucleatum) is known to be involved in the formation and development of periodontitis (Brennan and Garrett 2019). Outer membrane vesicles (OMVs) harboring toxic bacterial components are continuously released during F. nucleatum growth and regulate the extent of the inflammatory response by controlling the functions of immune and nonimmune cells in tissues (Briaud and Carroll 2020; Deo et al., 2020; Engevik 2020). Macrophages are important immune cells in periodontal tissue that resist pathogen invasion and play an important role in the pathophysiological process of periodontitis (Almubarak et al., 2020; Wang et al., 2021). However, the role of the interaction between F. nucleatum OMVs and macrophages in the occurrence and development of periodontitis has not been studied. The purpose of this study was to clarify the effect of F. nucleatum OMVs on the polarization of macrophages and the roles of this specific polarization and F. nucleatum OMVs in the pathophysiology of periodontitis.